The Academic Anxiety Level and Coping Mechanism of Seventh Graders in Public Secondary School - Torres, Sebastian Laurel M.; Bandol, Maria Divina D.; Dantes, Janelle B.; Lazatin, Chezter Aldrin A.; Tayag, Karen Joy Y.; Dominado, Noel L. (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
This study explored academic anxiety and coping strategies among seventh graders in a public secondary school. It aimed to assess anxiety levels, identify causes, and examine how students manage stress. Using a sequential explanatory design, 61 students were randomly selected from 360 seventh graders. Results showed moderate anxiety levels, mainly due to peer noise, high expectations, peer pressure, and heavy workloads. Students coped through study planning, positive thinking, and support from teachers and family, while some resorted to avoidance, worsening stress. The study emphasized the need for schools to provide interventions like awareness seminars and structured support to promote healthier coping strategies. Teachers also play a key role in reducing stress by fostering a supportive learning environment. The findings contribute to discussions on academic anxiety and can help shape educational policies to improve students’ well-being and success.